OLAHRAGA SEBAGAI KEKUATAN MEMBANGUN JIWA NASIONALIS MASYARAKAT PLURAL - Rizca Nur Hidayati (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2021)
Sport is part of the success of national development. Sports fostering and development must be placed in the mainstreaming of various government and local government policies at all lines and levels within the framework of the spirit of the nation. In the midst of the plurality of the Indonesian nation in race, ethnicity, culture and religion, sport is one of the means of unifying the nation. Our very diverse society competes in one arena, whether it is against fellow Indonesians, or with other nations from around the world, all of which blend into one. The research method used is descriptive qualitative. The use of a qualitative approach in research through descriptive analysis, the researcher wants to describe the concept of diversity nationalism and sports nationalism, the relationship between nationalism and sports and its manifestations in the field. This paper is a literature review on the phenomenon of sports nationalism in a diverse society. Sources of data come from scientific journals, book literature, official website which is then described by descriptive analysis. The results of the study show that exercise has broad benefits. Sports are often used as a tool for government and media to achieve national interests. Nationalism can be a source of motivation to achieve the best achievements as a gift to the nation and state. State institutions take sports programs that adapt and are friendly to socio-culture in East Java to integrate cultural sports synergy programs in uniting diversity. Multicultural culture comes to the surface, all soccer enthusiasts accept it as a new identity. Football no longer thinks about the backgrounds of the players, whether they are regional men or players from outside the region and region.